2019
DOI: 10.3390/lubricants7050046
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity in EHL Contacts with Water-Containing Gear Fluids

Abstract: Fluid friction in elastohydrodynamically lubricated (EHL) contacts depends strongly on the lubricant considered. Synthetic oils can have significantly lower fluid friction than mineral oils. Water-containing fluids have the potential to significantly reduce fluid friction further. The aim of this study is to investigate the film formation and frictional behavior of highly-loaded EHL contacts with water-containing fluids. Comparisons are made with mineral and polyalphaolefin oils. Measurements at an optical EHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
5
19
0
Order By: Relevance
“…This is commonly referred to as superlubricity (Hirano et al [15]). In addition, the film thickness measured at an EHL tribometer in [14] demonstrated a good lubricant film formation of water-containing gear fluids. A pressure-viscosity coefficient of approximately 6 1/GPa was derived.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is commonly referred to as superlubricity (Hirano et al [15]). In addition, the film thickness measured at an EHL tribometer in [14] demonstrated a good lubricant film formation of water-containing gear fluids. A pressure-viscosity coefficient of approximately 6 1/GPa was derived.…”
Section: Introductionmentioning
confidence: 89%
“…Recent investigations by the authors have shown that water-containing gear fluids can strongly reduce friction in elastohydrodynamically lubricated (EHL) contacts. Experimental investigations conducted by Yilmaz et al [14] at a twin-disk test rig show measured coefficients of friction smaller than 0.01 for a wide range of operating conditions. This is commonly referred to as superlubricity (Hirano et al [15]).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The considered lubricants were the same as used in preliminary basic study of the authors (Yilmaz et al [24]). Three water-containing gear fluids were compared with conventional gear oils.…”
Section: Lubricantsmentioning
confidence: 99%
“…In a study preliminary to the present study, the authors investigated the film formation and frictional behavior of highly-loaded EHL contacts with water-containing gear fluids in fluid film lubrication regime (Yilmaz et al [24]). Measurements at the optical EHL tribometer showed good lubricant film formation of the considered water-containing gear fluids due to their high pressure-viscosity coefficient and density.…”
Section: Introductionmentioning
confidence: 99%